Design and Implementation of MPPT System Based on PSO Algorithm - Calvinho, Gonçalo (2020)
This paper presents a method for maximum power point tracking (MPPT) based on the particle swarm optimization (PSO) algorithm with variable step size in order to prevent steady state oscillations. This will avoid the impact of partial shading conditions in the efficiency of photovoltaic (PV) systems. To optimize power output of the solar panels a DC-DC boost converter is used. Special emphasis is put on software development and implementation in the TMS320F28027 microcontroller in Texas Instruments Code Composer Studio.